Strategies of Islamic Religious Education Teachers in the Development of Teaching Materials - Aas Agustini; Undang Ruslan W (Al-Hayat: Journal of Islamic Education, 2021)
This research discusses Guru Pai's Strategy in The Development of Teaching Materials for Students at SDN Rengasdengklok Selatan 2. The type of research used is qualitative research. Research methods use interdisciplinary methods, including Management, pedagogical, sociological, and psychological methods. The primary data source of this study is the Teacher of Islamic Religious Education. Secondary data sources in this study are school profile data, theories on the concept of teaching materials development strategies, Master's Strategy Concepts in the Learning Process, and teaching materials development theory. Data collection using observations, interviews, and documentation. Data analysis uses the data reduction, data presentation, and withdrawal stages. Conclusion. The study results found that Islamic education learning strategies in the formation of Muslim personality students use two learning strategies, namely direct learning and indirect learning. Conclusions in the delivery of teaching materials in writing teaching materials to be more attractive, motivating, communicative, and help improve students' understanding of teaching and learning. Completeness of components, related to the package of teaching materials used as the main components, complementary components, and evaluation components of learning outcomes.